Methodological aspects of modeling household solid waste generation in Japan: Evidence from Okayama and Otsu cities. Issue 12 (December 2017) - Gu, Binxian; Fujiwara, Takeshi; Jia, Renfu; Duan, Ruiyang; Gu, Aijun
This paper presents a quantitative methodology and two empirical case studies in Japan on modeling household solid waste (HSW) generation based on individual consumption expenditure (ICE) and local waste policy effects by using the coupled estimation model systems. Results indicate that ICE on food, miscellaneous commodities and services, as well as education, cultural, and recreation services are mainly associated with the changes of HSW generation and its components in Okayama and Otsu from 1980 to 2014. The effects of waste policy measures were also identified. HSW generation in Okayama will increase from 11.60 million tons (mt) in 1980 to 25.02 mt in 2025, and the corresponding figures are 6.82 mt (in 1980) and 14.00 mt (in 2025) in Otsu. To better manage local HSW, several possible and appropriate implications such as promoting a green lifestyle, extending producer responsibility, intensifying recycling and source separation, generalizing composting, and establishing flexible measures and sustainable policies should be adopted. Results of this study would facilitate consumer management of low waste generation and support an effective HSW policy design in the two case cities. Success could lead to emulation by other Japanese cities seeking to build and maintain a sustainable, eco-friendly society. Moreover, the methodologies of establishing coupled estimation model systems could be extended to China and other global cities.